Modern Tracking Techniques for Monitoring, Controlling & Location Tracking: Improving Efficiency and Accuracy of Location Tracking and Control Systems (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Location tracking and control system require sufficient resource management as well as reduction in their Global System Of Mobile (GSM) network service cost. The data is transferred through GSM network by using SMS. This increases the system capability by efficiently managing tracking devices which could increase in number as time goes by Global Positioning System (GPS). It has become a common functionality in handheld devices, which is also known as Navstar GPS that provides geo-location and time information to a GPS receiver in all weather conditions, anywhere on or near the Earth where there is an unobstructed line of sight to four or more GPS satellites. and therefore, several location-tracking applications have been developed like GPS, GPRS, IMEI number, etc. Some techniques consume more time, less efficiency and more error rates. Location prediction is performed by using the current location, moving speed, and bearing of the target to predict its next location. When the distance between the predicted location and the actual location exceeds a certain starting point, the target transmits a short message to the tracker to update its current location.